HIGHER EDUCATION IN BRAZIL: DIDACTIC AND PEDAGOGICAL CHALLENGES OF UNIVERSITY TEACHING - Moreira, Carlos José de Melo; Moreira, Verônica Lima Carneiro (Seven Editora, 2025)
Contemporaneously, Brazilian higher education has faced multiple challenges involving political, didactic, and methodological dimensions. Democratization has expanded access, but inequalities, the precarization of the teaching career, and pressures of marketization still persist. The aim of this research is to analyze how these challenges impact university teaching practice, discussing limits and possibilities for consolidating a critical and innovative university pedagogy. The methodology adopted was qualitative and bibliographic, grounded in classical and contemporary authors of university pedagogy as well as official documents of public policies for higher education. As results, the study showed that university teaching has been reconfigured in the context of institutional expansion, inclusion policies, the need for pedagogical innovation, and the growing use of digital technologies and artificial intelligence. It was found that gaps remain in the pedagogical training of professors, which still lacks institutionalization. At the same time, methodological experiences and proposals capable of enhancing more critical, dialogical, and socially committed practices were identified. It is concluded that strengthening university pedagogy depends on faculty appreciation, investment in institutional conditions, and the critical integration of digital technologies. The research indicates that, despite the difficulties, there are concrete possibilities for transformation that may consolidate a more inclusive, innovative, and socially grounded university. DOI: https://doi.org/10.56238/sevened2025.038-006